Paper sovereigns : Anglo-Native treaties and the law of nations, 1604-1664 - Glover, Jeffrey (EBL-Schweitzer, 2014)
Paper Sovereigns demonstrates that treaty making and breaking in the early North Atlantic world involved complex struggles and crosscultural systems of negotiation, establishing Native American treaties as a powerful influence on European colonization.